Removal of Methylene Blue Dye from Water using Ecofriendly Waste Product (Eggshell) as an Adsorbent and Using the Optimum Adsorption Conditions with Real Water Sample from Tigris River - Fadhil, Dhuha H; Al-Hussin, Ahmed; Yousif, Emad (Al-Nahrain Journal of Science, 2019)
Environmental pollution is a worldwide issue that affects the human being health, water pollution is one of the causes of this phenomenon. Dyes represent the raw materials in many industries such as textile, paper, plastic and leather industries as well as they considered as toxic water pollutants. The adsorption method is one of the most effective methods for removing dyes from polluted water. In this search, ecofriendly food waste (eggshell) was used as an adsorbent for removing methylene blue dye (MB) from waste water. In this research, eggshell morphology was studied using Scanning Electron Microscopy (SEM) and Energy-Dispersive X-ray (EDX). The stability of the eggshell adsorbent was tested by Thermal Gravimetric Analysis (TGA). Whereas checking with various MB dye concentration for eggshell the maximum adsorption was noticed at (8ppm) and this concentration was used for further optimization. MB solutions was prepared at pH 7.2 and at 21℃ same conditions as in Tigris River water which was used to compare the activity of the eggshells adsorbent using analytical standard MB solutions and on the other hand using real sample solutions. The results show that using eggshells adsorbent with standards solution and real sample solutions of MB provide the same general trends with respect to MB removal. Consequently, using eggshell as an ecofriendly adsorbent was successfully tested to be used with both MB analytical standard solutions and real river MB solutions.